Traces across Time: Investigating an Unfinished Female Portrait by Sir Joshua Reynolds - Marcia Pointon (Interfaces)
A portrait by Sir Joshua Reynolds of an unidentified female sitter depicts only a face and a diamond breast jewel. Once owned by John Ruskin and then by Kenneth Clark, the portrait offers an opportunity to examine assumptions we make when discussing historic portraiture. What may we infer from the collectors who were drawn to this enigmatic object? How do judgements about sitters’ identities change? What is meant by finish? How might traces of ownership of a particular work - what we call ‘provenance’ - contribute to our understanding of the work itself? What can we tell from the material of a painting, that is, from its pigments and support, about how an artist ran his studio? How might accessories determine meaning? I disentangle and identify some of the assumptions taken for granted when discussing portraiture while at the same time re-evaluating a disputed and neglected work.